Great Bear Lake - Hunter, Erin. (New York, N.Y. : HarperCollinsPublishers, 2009)
Three bear cubs of different species are united for the first time as they begin their long journey in search of destiny, hope, and what it truly means to be a bear in the wild.
Keywords: Bears -- Juvenile fiction; Bears -- Fiction; Fantasy; Fantasy fiction